2002
DOI: 10.1080/1042819021000006295
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin and Meisoindigo in the Treatment of Chronic Myelogenous Leukemia in China

Abstract: The aim of this review is to summarize our experience and the current knowledge on the clinical results of Indirubin, a minor active constituent of a well-know traditional Chinese prescription, Ganggui Luhui Wan, and its analogue, Meisoindigo, in the treatment of chronic myelogenous leukemia (CML) in China. Indirubin and meisoindigo induced hematologic remission in patients with chronic phase (CP) CML as effective as hydroxyurea and busulfan, in addition, there were no significant differences in median duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
212
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(214 citation statements)
references
References 3 publications
0
212
1
1
Order By: Relevance
“…21,23 Indirubin and its derivatives have been reported to function as protein kinase inhibitors by interacting with the kinase ATP-binding pocket. 23,44,49,50 Numerous studies have also commented on its activity in maintaining the self-renewal and pluripotency of embryonic stem cells through activating the Wnt/b-catenin pathway and in promoting the proliferation of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,23 Indirubin and its derivatives have been reported to function as protein kinase inhibitors by interacting with the kinase ATP-binding pocket. 23,44,49,50 Numerous studies have also commented on its activity in maintaining the self-renewal and pluripotency of embryonic stem cells through activating the Wnt/b-catenin pathway and in promoting the proliferation of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-AR oligos (AR-ASOs) have recently been developed that effectively repress AR expression at both the mRNA and the protein level in preclinical prostate cancer models, 18,19 However, a phase 1 study of a PS LNA gapmer anti-AR-ASO in patients with advanced prostate cancer demonstrated only a limited number of PSA responses and significant dose-related toxicity. 20 In this study, we discovered that the small molecule 6-bromo-indirubin-3 0 -oxime (6BIO), an anti-leukemia indirubin derivative, 21 possesses multiple anti-prostate cancer activities. 6BIO has been reported to regulate cellular viability, proliferation, and apoptosis and act as an anti-tumor agent in a variety of human cancer models, including melanoma, 22 breast cancer, 23 bladder cancer, 24 and lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Indirubin (1a, Scheme 1) is a natural bis-indol molecule found in plants and mollusks [21]. It has demonstrated antileukemic properties, although the exact mechanism of this remains unclear [22]. Modifications of indirubin have lead to the discovery of other potential anticancer compounds [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has demonstrated antileukemic properties, although the exact mechanism of this remains unclear [22]. Modifications of indirubin have lead to the discovery of other potential anticancer compounds [20,[22][23][24]. The indirubin family of compounds target several kinases, some of which have been co-crystallised with indirubin analogues: GSK3, CDK2, CDK5, PfPK5 [18,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a renovated needs of indigo plants because of the demand for natural dyes and daily necessities such as soap and plastic products (Velho et al, 2017). Indigo is also used in traditional Chinese medicines to treat systemic psoriasis and leukemia (Koo & Arain, 1998;Xiao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%